2007
DOI: 10.1002/mabi.200600223
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Refinery as the Bio‐Inspired Process to Bulk Chemicals

Abstract: This paper describes several examples of knowledge-intensive technologies for the production of chemicals from biomass, which take advantage of the biomass structure in a more efficient way than the production of fuels or electricity alone. The depletion in fossil feedstocks, increasing oil prices, and the ecological problems associated with CO(2) emissions are forcing the development of alternative resources for energy, transport fuels, and chemicals, such as the replacement of fossil resources with CO(2) neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
182
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 7 publications
0
182
0
2
Order By: Relevance
“…1; Sanders et al, 2007). This route requires non-renewable petrochemical products as raw materials and relatively harsh reaction conditions, as well as expensive catalyst systems.…”
mentioning
confidence: 99%
“…1; Sanders et al, 2007). This route requires non-renewable petrochemical products as raw materials and relatively harsh reaction conditions, as well as expensive catalyst systems.…”
mentioning
confidence: 99%
“…A detailed study of the solubility behavior of CGP isolated from recombinant E. coli in inorganic salts has been carried out by Füser and Steinbüchel (16). It was shown that the occurrence of the soluble form was not dependent on the origin of cphA or on the host.Recently, several putative applications for CGP and its derivatives have become available, indicating there is a need for its efficient biotechnological production (36,42,43). For the production of CGP at a technical scale, cyanobacteria were shown to be unsuitable due to their low cell densities and polymer contents (3.5% [wt/wt]) and slow growth and circumstantial growth conditions in a photobioreactor (18,19 Also, in the industrially relevant bacteria Pseudomonas putida, Ralstonia eutropha, and Corynebacterium glutamicum, considerable amounts of CGP could be produced after heterologous expression of cphA (3,13,48,49).…”
mentioning
confidence: 99%
“…Recently, several putative applications for CGP and its derivatives have become available, indicating there is a need for its efficient biotechnological production (36,42,43). For the production of CGP at a technical scale, cyanobacteria were shown to be unsuitable due to their low cell densities and polymer contents (3.5% [wt/wt]) and slow growth and circumstantial growth conditions in a photobioreactor (18,19).…”
mentioning
confidence: 99%
“…The corrosivity of the liquid would lead to destroying the container or equipment. Fortunately, a hydrothermal process can be introduced to decrease the acidity and oxygen content in the liquid products for the sake of improving the quality of the liquid products which can be converted to biodiesel [16,18].…”
Section: Probable Organic Compoundsmentioning
confidence: 99%